2008
DOI: 10.1590/s0100-879x2008005000021
|View full text |Cite
|
Sign up to set email alerts
|

A majority of Brazilian patients with rheumatoid arthritis HLA-DRB1 alleles carry both the HLA-DRB1 shared epitope and anti-citrunillated peptide antibodies

Abstract: The objective of the present study was to evaluate the contribution of the shared epitope (SE), the rheumatoid arthritis (RA) protection model, and the occurrence of anti-cyclic citrullinated peptide (anti-CCP) antibodies in RA patients from a genetically diverse population. One hundred and forty Brazilian RA patients and 161 matched controls were typed for HLA-DRB1 alleles using amplified DNA hybridized with sequence-specific oligonucleotide probes or primers. Patients were stratified according to the presenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
13
1
3

Year Published

2009
2009
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 36 publications
9
13
1
3
Order By: Relevance
“…It was recently shown that HLA-DRB1 SE alleles are associated with increased levels of anti-citrullinated protein antibodies (ACPA) in Caucasian RA patients [15], [16], [17], [18]. It is unclear, however, whether this selective association between ACPA-positive RA and certain HLA-DRB1 alleles is valid in all ethnic groups, in particular in groups with distribution of HLA-DRB1 alleles different from those described in Caucasians.…”
Section: Introductionmentioning
confidence: 99%
“…It was recently shown that HLA-DRB1 SE alleles are associated with increased levels of anti-citrullinated protein antibodies (ACPA) in Caucasian RA patients [15], [16], [17], [18]. It is unclear, however, whether this selective association between ACPA-positive RA and certain HLA-DRB1 alleles is valid in all ethnic groups, in particular in groups with distribution of HLA-DRB1 alleles different from those described in Caucasians.…”
Section: Introductionmentioning
confidence: 99%
“…27 It has also been proposed that certain HLA-DRB1 alleles protect against development of RA, compared with other HLA-DRB1 non-SE alleles. Proposed protective motifs include: the 70 DERAA 74 sequence, [28][29][30][31] aspartic acid at position 70 (D 70 ), 32,33 , isoleucine at position 67 (I 67 ) 34 or S 1 ( 71 ERAA 74 (S 1E ) with 71 ARAA 74 (S 1A )). 18,20,35 S 3D ( 70 DRRAA 74 ) was 'neutral'.…”
Section: Introductionmentioning
confidence: 99%
“…One of the successful examples of replication is the association between HLA-DRB1 and susceptibility to RA that has been replicated repeatedly among Caucasian, Asian and other ethnic populations 10 11 12 . HLA-DRB1 is now considered as the strongest genetic factor for RA in most ethnic populations.…”
mentioning
confidence: 99%